2015
DOI: 10.4314/ahs.v15i2.8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the diagnostic performance and operational characteristics of four rapid immunochromatographic syphilis tests in Burkina Faso

Abstract: Background and objective: Little information is available on the rapid diagnostic testing for syphilis in Burkina Faso. The objectives of the study were (i) to assess the sensitivity and specificity of four on site rapid tests in comparison with Treponema pallidum haemagglutination assay (TPHA) as a gold standard and (ii) to evaluate the operational characteristics of those tests among health workers in a maternity unit. Methods: Four rapid syphilis tests commercially available in Burkina Faso were evaluated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 13 publications
1
15
2
2
Order By: Relevance
“…Several studies have different specificity and sensitivity values ​​with the SD Bioline Syphilis 3.0 test. Sensitivity values ​​very close to those found in the present study were reported by Herring et al 23 who found 95.0%; Benzaken et al 26 90.2%; Dlamini et al 27 90.1%; Causer et al 21 87.8%; Bocoum et al 28 90%; and Mehra et al 29 92.9%. As for specificity values, the same authors found 94.9%, 99.4%, 98.0%, 98.5%, 98.0% and 98.3%, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have different specificity and sensitivity values ​​with the SD Bioline Syphilis 3.0 test. Sensitivity values ​​very close to those found in the present study were reported by Herring et al 23 who found 95.0%; Benzaken et al 26 90.2%; Dlamini et al 27 90.1%; Causer et al 21 87.8%; Bocoum et al 28 90%; and Mehra et al 29 92.9%. As for specificity values, the same authors found 94.9%, 99.4%, 98.0%, 98.5%, 98.0% and 98.3%, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…These rapid tests for syphilis screening are available in Burkina Faso, and four of them have had their performance and operational characteristics assessed [12]. Unfortunately they are not widely adopted for ANC services.…”
Section: Introductionmentioning
confidence: 99%
“…Positive samples were consecutively tested with a Rapid Plasma Reagin (RPR-CHARBON®) test kit ( BIOLABO SAS, French ), a nontreponemic test [ 30 ]. Alere Determine™ Syphilis TP is a qualitative in vitro immune-chromatographic test detecting antibodies against the Treponema pallidum bacteria in patient's serum, plasma, and whole blood [ 31 ]. Positivity to the Alere Determine™ Syphilis TP test reveals the presence of antibodies against the Treponema pallidum bacteria indicating the presence of either previous, acute, or treated syphilis.…”
Section: Methodsmentioning
confidence: 99%